Comparative Study of Post Operative Astigmatism Following Small Incision Cataract Surgery-Sics in Superior, Supero-Temporal and Temporal Incision. (Medicine Today, 2014)
This prospective study was designed to evaluate and compare surgically induced astigmatism in small incision cataract surgery through superior, supero-temporal and temporal approach. Astigmatism means no point focus. It is a refractive error that occurs when the optical system does not have the same refractive power at all its meridian. The location and width of incision will determine the amount of surgically induced astigmatism (SIA) in small incision cataract surgery. Temporal and superotemporal incisions are less likely to induce post operative astigmatism than the 12 o' clock incisions. The study was carried out at Tairunnessa Memorial Medical College and Hospital, Gazipur, Faridpur Diabetic Association Medical College and Hospital, Faridpur and General Hospital, Faridpur, Bangladesh, from January 2012 to June 2013.Total number of 120 eyes of 108 patients, both male and female patients were included for the study. We excluded the patients having corneal scar, irregular astigmatism, presence of pterygium and previous intraocular surgery from our study. The mean patient age at the time of surgery was 61.9±8.1 years ranged from 40 to 70 years.The patients were divided into three groups.The three groups had 40 patients each. The patients in group-A underwent manual SICS with a superior incision, the patients in group-B underwent manual SICS with a supero-temporal incision and the patients in group-C underwent manual SICS with a temporal incision. The small incision cataract surgeries were done by applying same surgical technique.The courses of the post operative astigmatic changes were determined by using Auto Refracto Keratometer at 1st week, 6th weeks and 12th week postoperatively. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17925 Medicine Today 2013 Vol.25(2): 72-74